Produção de biodiesel a partir de matéria-prima com alto teor de acidez: modelagem cinética e termodinâmica, simulação e otimização - Brondani, Leoni Nogueira (2022)
This work proposes to investigate the methyl esters production through the transesterification reaction of oleic acid with methyl acetate catalyzed by niobium phosphate. For the autogenous batch reaction system, at high temperatures and pressures, a mathematical model was proposed considering simultaneously the influences of the compounds volatilization, reaction kinetics, phase equilibrium and chemical equilibrium. Different kinetic and thermodynamic modeling approaches were applied, tested and had their parameters estimated. Experimental data under conditions of coexistence of vapor-liquid phases were obtained by varying the temperature, molar ratio and initial reaction volume. The hypotheses adopted by the model were statistically evaluated, moreover, the main hypothesis about the influence of volatilization being very relevant to guarantee the adjustment of the model, whose use proved to be necessary mainly in experimental conditions with different initial ratios of reaction volume/headspace. The first order reversible pseudo-homogeneous model concomitantly with the thermodynamic model of the “φ-φ” type using the Peng-Robinson equation of state and the van der Waals mixing rule with two binary interaction parameters was able to represent the experimental data. Afterwards, to overcome the chemical equilibrium limitation to the system, a two-step sequential process (reaction and separation) was proposed, studied and had its operational conditions optimized. The optimization procedure was carried out using the proposed mathematical model and aiming at the highest productivity of the intensification process, so that, at the end, it was obtained the requirement of a biodiesel standard content of free fatty methyl esters (96.5% m/m). In the end, the optimal productivity values and their optimal operating conditions were presented and had experimental data to validate them. In this way, the proposed intensification process proved to be a viable and effective alternative for the production of biodiesel with the minimum specification of esters from the heterogeneous transesterification of oleic acid and methyl acetate.